Multiple Viral microRNAs Regulate Interferon Release and Signaling Early during Infection with Epstein-Barr Virus - Bouvet, Mickaël (mBio, 2021)
Epstein-Barr virus (EBV), a human herpesvirus, encodes 44 microRNAs (miRNAs), which regulate many genes with various functions in EBV-infected cells. Multiple target genes of the EBV miRNAs have been identified, some of which play important roles in adaptive antiviral immune responses. Using EBV mutant derivatives, we identified additional roles of viral miRNAs in governing versatile type I interferon (IFN) responses upon infection of human primary mature B cells. We also found that Epstein-Barr virus-encoded small RNAs (EBERs) and LF2, viral genes with previously reported functions in inducing or regulating IFN-I pathways, had negligible or even contrary effects on secreted IFN-α in our model. Data mining and Ago PAR-CLIP experiments uncovered more than a dozen previously uncharacterized, direct cellular targets of EBV miRNA associated with type I IFN pathways. We also identified indirect targets of EBV miRNAs in B cells, such as TRL7 and TLR9, in the prelatent phase of infection. The presence of epigenetically naive, non-CpG methylated viral DNA was essential to induce IFN-α secretion during EBV infection in a TLR9-dependent manner. In a newly established fusion assay, we verified that EBV virions enter a subset of plasmacytoid dendritic cells (pDCs) and determined that these infected pDCs are the primary producers of IFN-α in EBV-infected peripheral blood mononuclear cells. Our findings document that many EBV-encoded miRNAs regulate type I IFN response in newly EBV infected primary human B cells in the prelatent phase of infection and dampen the acute release of IFN-α in pDCs upon their encounter with EBV.